Pengaruh Latihan Keseimbangan Dengan Trampolin Terhadap Peningkatan Keseimbangan Tubuh Pemain Bola Basket Unit Bola Basket Universitas Muhammadiyah Surakarta - kalma, kukut lestapa; , Dwi Rosella Komala Sari, S.Fis., M.Fis. Dipil.Cidesco (2015)
Background : A basketball player should had excellent stamina, it was also expected to had an agility and ability to maintain balance of the his body during playing basketball. The players who can more maintaining balance of his body will reduce risk of fall after jumping to put a ball into the ring. One of training variation to balancing body use a trampoline. The objective purpose : was to know influence of Body Balances training with a Trampoline to Increace Body Balance Of Basketball Players of Muhammadiyah University of Surakarta. Method of research : this study used one group pre-test and post-test with group design, with total sample 14 basketball players as treatment group , and 14 players as control group. treatment used a trampoline balance with duration of exercise as much as 3 times a week for 4 sunday with the duration of exercise 2 until 3 minutes and 2 set of variations position. The measurement of a balance using stork stand the test. Comparative test data analysis using the wilcoxon signed ranks test. The results : there were treatment group with pre test, average of balance was 4,84 second and post test 9,06 second. Group control, average of balances in pre test was 4,96 second, post test 5,38 second. Result of statistic test, the difference from average of time from two groups with p = 0,000 Conclusion : there were Influence of Body Balances With a Trampoline to Increace Balance Of Basketball Players of Muhammadiyah University of Surakarta Keywords: balance, trampoline, basketball players